2020
DOI: 10.3390/mi11121107
|View full text |Cite
|
Sign up to set email alerts
|

Propulsion Mechanism of Flexible Microbead Swimmers in the Low Reynolds Number Regime

Abstract: A propulsion mechanism for a flexible microswimmer constructed from superparamagnetic microbeads with different diameters and subjected to an oscillating field was studied experimentally and theoretically herein. Various types of artificial swimmers with different bending patterns were fabricated to determine the flexibility and an effective waveform for a planar beating flagellum. Waveform evolutions for various swimmer configurations were studied to determine the flexible mechanism of the swimmers. A one-arm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…These swimmers of varying bead diameters achieve nonreciprocal motion because of structural deformation within its cyclic motion 21 . However, the assembled structure of these flexible swimmers are found to be unstable and achieve low propulsion efficiencies 22 . It has been shown that for non‐flexible swimmers, while the shape of an object is essential, the orientation of its transverse magnetic dipole governs swimming 23 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These swimmers of varying bead diameters achieve nonreciprocal motion because of structural deformation within its cyclic motion 21 . However, the assembled structure of these flexible swimmers are found to be unstable and achieve low propulsion efficiencies 22 . It has been shown that for non‐flexible swimmers, while the shape of an object is essential, the orientation of its transverse magnetic dipole governs swimming 23 .…”
Section: Introductionmentioning
confidence: 99%
“…21 However, the assembled structure of these flexible swimmers are found to be unstable and achieve low propulsion efficiencies. 22 It has been shown that for non-flexible swimmers, while the shape of an object is essential, the orientation of its transverse magnetic dipole governs swimming. 23 Recently magnetic microspheres that form rigid assemblies-termed achiral microrobots 24 have been shown to propel themselves when subject to an external magnetic torque.…”
Section: Introductionmentioning
confidence: 99%